2010
DOI: 10.2353/ajpath.2010.100279
|View full text |Cite
|
Sign up to set email alerts
|

Evidence of Oxidative Stress in the Pathogenesis of Fuchs Endothelial Corneal Dystrophy

Abstract: Fuchs endothelial corneal dystrophy (FECD) is a progressive, blinding disease characterized by corneal endothelial (CE) cell apoptosis. Corneal transplantation is the only measure currently available to restore vision in these patients. Despite the identification of some genetic factors, the pathophysiology of FECD remains unclear. In this study, we observed a decrease in the antioxidant response element-driven antioxidants in FECD corneal endothelium. We further demonstrated that nuclear factor erythroid 2-re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

18
267
0
6

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 267 publications
(291 citation statements)
references
References 52 publications
18
267
0
6
Order By: Relevance
“…In this regard, mutations in TERE1 that reduce APOE binding may impair cholesterol and lipid recycling by APOE, and lead to elevated intracellular cholesterol via reduced efflux (Prack et al, 1994;Heeren et al, 2004;Abildayeva et al, 2006;Ha et al, 2009). It may also raise basal oxidative stress, consistent with recent reports regarding pathogenesis of SCD and other corneal dystrophies (Gatzioufas et al, 2010;Jurkunas et al, 2010).…”
Section: Implications Of Tere1 Protein Interactions With Apoesupporting
confidence: 81%
“…In this regard, mutations in TERE1 that reduce APOE binding may impair cholesterol and lipid recycling by APOE, and lead to elevated intracellular cholesterol via reduced efflux (Prack et al, 1994;Heeren et al, 2004;Abildayeva et al, 2006;Ha et al, 2009). It may also raise basal oxidative stress, consistent with recent reports regarding pathogenesis of SCD and other corneal dystrophies (Gatzioufas et al, 2010;Jurkunas et al, 2010).…”
Section: Implications Of Tere1 Protein Interactions With Apoesupporting
confidence: 81%
“…Oxidative stress and apoptosis are reported to play a role in the development of FECD particularly in regard to accelerated corneal endothelial cell loss (Borderie et al 2000;Li et al 2001;Buddi et al 2002;Szentmáry et al 2005;Engler et al 2010;Jurkunas et al 2010;Azizi et al 2011). This may be in part due to chronic ultraviolet (UV) light exposure (Inoki et al 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Both association and linkage studies showed that a polymorphism in the transcription factor 4 (TCF4) gene was associated with FECD (Baratz et al 2010;Li et al 2011). Apoptosis was shown to be involved in the pathogenesis of KC and FECD (Mohan et al 1997;Cho et al 1999;Kim et al 1999;Borderie et al 2000;Li et al 2001;Kaldawy et al 2002;Gottsch et al 2003;Szentmáry et al 2005;Joyce et al 2009;Engler et al 2010;Jurkunas et al 2010). It was also shown that the FAS/FASLG system is expressed in the cornea and might have important functions in normal corneal physiology and in the pathophysiology of corneal diseases, including modulation of keratocyte apoptosis after epithelial injury (Wilson et al 1996).…”
Section: Introductionmentioning
confidence: 99%
“…44 Interestingly, several authors have found evidence of increased apoptosis having a role in endothelial cell loss, as observed in FECD. 46,47 Furthermore, it was shown that the defense mechanism of FECD endothelium against oxidative stress-induced damage is impaired when compared with normal cells, 39,45,48,49 which is supported by the observed significant higher levels of (baseline) oxidative stressinduced damage, 43,45,48 and changes in endothelial cell morphology characteristic for oxidative stress. 50 These data suggest that chronic oxidative stress contributes to the pathophysiology of FECD, and that the decreased defense system renders FECD endothelial cells even more susceptible to oxidative stress-induced damage than normal cells already are.…”
Section: Pathophysiology Of Fecdmentioning
confidence: 91%
“…[40][41][42] Corneal endothelial cells are thought to be especially vulnerable to oxidative stress-induced damage because they do not proliferate and have a high level of metabolic activity owing to their pump function. 39,43 Fortunately, these cells have several defense mechanisms against the detrimental effects of oxidative stress, 44,45 thereby reducing damage and promoting cell survival. However, if oxidative stress persists, the defense mechanisms fail, thereby allowing the cell to accumulate damage.…”
Section: Pathophysiology Of Fecdmentioning
confidence: 99%